PERBEDAAN EFEKTIFITAS PENGGUNAAN ATRAKTAN LARUTAN FERMENTASI GULA-RAGI DAN AIR RENDAMAN CABAI MERAH (Capsicum Annum) TERHADAP JUMLAH TELUR Aedes Sp. YANG TERPERANGKAP - Arvita Kumala Sari; Devi Octaviana; Siwi Pramatama Mars Wijayanti (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2017)
Oviposition trap (Ovitrap) is one of the Aedes sp mosquito controlling method without insectide. The purpose of this study was to determine the effectiveness of the use of attractant solution of yeast- sugar and water soaking red chilii to the number of trapped eggs of Aedes sp. Type of this research was experimental study. The subject of this research were all the eggs were trapped on ovitrap, while the research unit was a group of houses, building / construction in the research area which consisted of 15 houses. The study was conducted in kelurahan Mersi,Mersi District of Purwokerto. This research applies 3 treatment, so that the object consists of 15 houses with the total number of installed ovitrap 45 indoors and 45 outdoors. Total number of eggs of Aedes sp which trapped in ovitrap were 1021 grain. Number of trapped eggs in control (water wells), water of soaking red chili attractant and solution of yeast-sugart attractant were 929 grains (91%), 60 grains (5,9%) and 32 grains (3.1%) respectively. Number of eggs which trappped in ovitrap outdoor were 639 grains (62.6%) while in ovitrap indoor wwere 382 grains (37.4%). There was significant difference in the number of eggs that trapped in each type of attractant, however there was no significant difference in the number of eggs that are trapped on the basis of location.